Assessment Model Impact of Climate Change on Potential Production for Food and Energy Needs for the Coastal Areas of Bengkulu, Indonesia - Eko Sumartono; Gita Mulyasari; Ketut Sukiyono (Agro Bali : Agricultural Journal, 2021)
Bengkulu is said to be the center of the world's climate because of the influence of water conditions and the topography of the area where the rain cloud formation starts. The waters in Bengkulu Province become a meeting place for four ocean currents which eventually become an area where the evaporation process of forming rain clouds becomes the rainy or dry season and affects the world climate. Method to analyze descriptively, shows oldeman Classification and satellite rainfall estimation data is added. In relation to the Analysis of Potential Food Availability for the Coastal Areas of Bengkulu Province uses a quantifiable descriptive analysis method based. The results show that most are included in the Oldeman A1 climate zone, which means it is suitable for continuous rice but less production due to generally low radiation intensity throughout the year. In an effort to reduce or eliminate the impact of climate change on food crop production, it is necessary to suggest crop diversification, crop rotation, and the application of production enhancement technologies. Strategies in building food availability as a result of climate change are: First, develop food supplies originating from regional production and food reserves on a provincial scale. Second, Empowering small-scale food businesses which are the dominant characteristics of the agricultural economy, especially lowland rice and horticultural crops. Third, Increase technology dissemination and increase the capacity of farmers in adopting appropriate technology to increase crop productivity and business efficiency. Four, Promote the reduction of food loss through the use of food handling, processing and distribution technologies.